Family is the Main Factor of Society (European Journal of Pedagogical Initiatives and Educational Practices, 2023)
This article focuses on the role of the family and its role in the development of society in the processes of information and digital technologies in our country, the historical and moral foundations of family relations and views and imaginations in this regard, as well as the reforms that are being carried out in the family today from a historical point of view.